(X-9)/6=(x+2)/7

Simple and best practice solution for (X-9)/6=(x+2)/7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X-9)/6=(x+2)/7 equation:



(X-9)/6=(X+2)/7
We move all terms to the left:
(X-9)/6-((X+2)/7)=0
We calculate fractions
X/()+(-((X+2)*6)/()=0
We calculate terms in parentheses: +(-((X+2)*6)/(), so:
-((X+2)*6)/(
We multiply all the terms by the denominator
-((X+2)*6)
We calculate terms in parentheses: -((X+2)*6), so:
(X+2)*6
We multiply parentheses
6X+12
Back to the equation:
-(6X+12)
We get rid of parentheses
-6X-12
Back to the equation:
+(-6X-12)
We get rid of parentheses
X/()-6X-12=0
We multiply all the terms by the denominator
X-6X*()-12*()=0
We add all the numbers together, and all the variables
X-6X*()=0

See similar equations:

| a/21+5/7=2/14 | | -3(k-5)=2(k-10) | | 1.50+2x=10.50 | | 3+5b+4=2 | | 4x^2+3x+1=77 | | 4b+1300=40b-86 | | 2(x-6)=4x-4 | | -6x-21=19x+6 | | 4x-16/7=7x/12 | | 2m^2=60-7m | | 1-4m+2m=-7 | | 0+x-(2-x)=-2(-2x-4) | | n÷2-4=2 | | 4(x-4)/7=7x/12 | | (q+9)(q+8)=0 | | 5-3=12x+4 | | -10=5x+6+3x | | -5t^2+5t=0 | | 4/5x=3/8 | | 4+3×=20-5x | | 35x(35x)=365 | | 3(p+2)=2(p-3)+8 | | -10d-20=-19d+2+20d | | 35x+35x=365 | | 3x+4=2-6 | | 2n^2-138=11n | | 3(3/4a+3)=87 | | 8=4n+8+10n | | 4+x-1/2x=47 | | 008(y-1)+0.06y=0.04y-0.2 | | -20d+13=-19d+2+20d | | 6/x=24/4 |

Equations solver categories